Lessons from a pilot for uncontrolled donation after circulatory death in the ED in the UK. Issue 3 (22nd November 2019) - Reed, Matthew James; Currie, Ian; Forsythe, John; Young, Irene; Stirling, John; Logan, Lesley; Clegg, Gareth R; Oniscu, Gabriel C
Abstract : Worldwide there is a shortage of available organs for patients requiring transplants. However, some countries such as France, Italy and Spain have had greater success by allowing donations from patients with unexpected and unrecoverable circulatory arrest who arrive in the ED. Significant advances in the surgical approach to organ recovery from donation after circulatory death (DCD) led to the establishment of a pilot programme for uncontrolled DCD in the ED of the Royal Infirmary of Edinburgh. This paper describes the programme and discusses the lessons learnt.